Bilateral transversus abdominis plane block as a sole anesthetic technique in emergency surgery for perforative peritonitis in a high risk patient - Lipi Mishra; Nibedita Pani; Debasis Mishra; Nupur Patel (Wolters Kluwer Medknow Publications, 2013)
Although transversus abdominis plane (TAP) block is an effective way of providing analgesia in post-operative abdominal surgery patients; however, it can be considered as an anesthetic technique in high-risk cases for surgery. We report a case of a geriatric female with chronic obstructive pulmonary disease in the respiratory failure, hypotension, posted in an emergency with old perforation leading to peritonitis. The surgery was successfully conducted under bilateral TAP block, which was used as a sole anesthetic technique. TAP block can be considered as an anesthetic technique for abdominal surgery in moribund patients.